The Correlation Between Social Media use and the Stigma of Covid-19 in Adolescents - Sri Sunarti; Nida Amalia; Rusni Masnina; Muhammad Dodi Rahman; Eny Etika Raisha; Ferry Adiaksyah; Rida Sri Wahyuni; Badrani Abbas Al-Fajri (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
The limited space for people to move during the COVID-19 pandemic has made people depend a lot on activities carried out online, including students who cannot study offline. Using social media is something that students at SMAN 7 Samarinda do almost every day, with a lot of news about COVID-19 spreading on the internet, which is not necessarily true, it can create a stigma against COVID-19.This study uses a quantitative research design and uses a Cross Sectional method. Data collected was using an electric questionnaire (google form). The sampling technique used in this research Stratified random sampling. The population in this research, sample was 154 students. The results in this study, obtained respondents with high use of social media amounted to 81 people (52.6%) and the number of respondents with low use of social media amounted to 73 people (47.4%). respondents with high stigma were 96 people (62.3%) and the results of low stigma were 58 people (37.7%). According to the results of statistical tests using the test, there was no significant relationship between the use of social media and negative stigma against COVID-19 in adolescent students of SMA Negeri 7 Samarinda. High use of social media has an effect on the positive stigma of Covid 19